2008
DOI: 10.1007/s11187-008-9098-x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of equity finance for R&D activity

Abstract: R&D activity, Equity finance, Small- and medium-sized enterprises, G 32, O 32, L 26,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 63 publications
(50 reference statements)
3
47
0
1
Order By: Relevance
“…The empirical evidence obtained in this study corroborates the conclusions of Mueller (1986), since profitability is persistent in the case of young and old SMEs. This may be due to the dynamic profile of the existing markets, thereby small divergences occurring at certain times can be solved by firms entering and leaving the markets.…”
Section: Discussion Of the Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The empirical evidence obtained in this study corroborates the conclusions of Mueller (1986), since profitability is persistent in the case of young and old SMEs. This may be due to the dynamic profile of the existing markets, thereby small divergences occurring at certain times can be solved by firms entering and leaving the markets.…”
Section: Discussion Of the Resultssupporting
confidence: 87%
“…According to Mueller (1986), there is a propensity of firm profitability persistence over time, i.e., a statistically significant relationship between firm profitability in the previous period and firm profitability in the present period. That author argues that this occurs because the possible small divergences between profitability in the previous and present periods are immediately cancelled out by the entry and exit of firms in the market.…”
Section: Profitability In the Previous Periodmentioning
confidence: 99%
“…Although business angels are heterogeneous in their individual characteristics, most studies agree that it is after having invested, through their involvement in the venture, that they create value, as evidenced in studies of the perceptions of venture founders (Lindström and Olofsson 2001;Lindström and Olofsson 2002;Müller and Zimmermann 2009), as well as in quantitative studies wherein it is demonstrated that the number of negative exits are reduced (Wiltbank 2005). While this value creation has attracted considerable interest, most post-investment business angel research has been descriptive (Harrison and Mason 2008a), and post-investment involvement has been described as a black box (De Clerq and Manigart 2007).…”
Section: Introductionmentioning
confidence: 99%
“…La existencia de restricciones a la financiación tiene una gran relevancia por cuanto puede obligar a muchos emprendedores potenciales a renunciar a proyectos de inversión viables, de calidad y con apuesta de futuro (Iruarrizaga & Santos, 2010). En este contexto, las empresas jóvenes presentan más restricciones financieras que aquellas que ya tienen una posición en el mercado (Müeller & Zimmermann, 2009). …”
Section: Emprendimiento Y Acceso a La Financiaciónunclassified